Blunted Reward Sensitivity and Trait Disinhibition Interact to Predict Substance Use Problems. (September 2019) - Joyner, Keanan J.; Bowyer, Colin B.; Yancey, James R.; Venables, Noah C.; Foell, Jens; Worthy, Darrell A.; Hajcak, Greg; Bartholow, Bruce D.; Patrick, Christopher J.
Reward-deficit models of addiction posit weaknesses in reward sensitivity to be promotive of substance dependence, whereas the externalizing spectrum model views substance problems as arising in large part from a general disinhibitory liability. In the current study we sought to integrate these perspectives by testing for separate and interactive associations of disinhibition and reward dysfunction with interview-assessed substance use disorders (SUDs). Community and college adults ( N = 199) completed a scale measure of trait disinhibition and performed a gambling-feedback task yielding a neural index of reward sensitivity, the "Reward Positivity" (RewP). Disinhibition and blunted RewP independently predicted SUDs and also operated synergistically, such that participants—in particular, men—with high levels of disinhibition together with blunted RewP exhibited especially severe substance problems. Though limited by its cross-sectional design, this work provides new information about the interplay of disinhibition, reward processing, and gender in SUDs and suggests important directions for future research.